The role of institutions and development: the political economy of Malaysia's industrial policy-making / Firdausi Suffian - Suffian, Firdausi (Universiti Teknologi MARA, 2019)
This paper explores the politics and political economy of Malaysia's industrial policy-making processes. Neo-institutionalism and developmental state approach are used to construct the industrial policy-making framework in Malaysia setting. Given the limitation of rational choice approach, historical and sociological institutionalism was used as paradigm to understand the role of institutions. Central to developmental state approach which are political elite, bureaucracy and close reciprocal relationship with 'selected' enterprises play crucial role to devise industrial policy. However, the role of institutions that has its roots in history, political events, power relations and norms can influence the interactions and organization of the economic actors. Institutional arrangement in policy-making can be different in every country, as variations of institutional designs have always been the principle reason for different countries adopts different industrial policy. This paper highlights on how principle policy actors which act as 'triangular arrangement' can mobilize, coordinate, and priorities economic preferences in Malaysia policy-making institutions.